Tourism Investment, Supply and Demand in Indonesia: Impact and Factor Analysis - Faurani Santi; Rina Oktaviani; Dedi Budiman Hakim; Reni Kustiari (UBL, 2013)
Tourism is one of the most significant contributors to the Indonesia growth of economy, based on datafrom the Indonesia Central Bureau of Statistics in 2012, the share of national tourism to GDP is 13.9percent and of course the contribution of the sector to be helpful for the growth of the national economy,through foreign exchange earnings as revenue from tourist consumption. Besides that, it has provided amultiplier effect to other sectors which related to the sectors. Therefore, an improving of the contributionis a one of government’s effort to boost economic growth and increasing the welfare, thus the increasingof tourism investment and trade will be focus in the tourism development program. Meanwhile, theIndonesia Coordinating Board (BKPM) stated the average national investment for the tourism sector isRp. 2.73 billion or 6 percent from total investment during 2006-2012, in other words an investment intourism sector has not been able to provide optimal contribution to the national economy developmentconsidering to its potential.The purpose of this study was to analyze the determinants of investment, demand and supply ofIndonesian tourism sector. Regarding to answer the problems, this research used series data from 1990 –2012 periods, by using simultaneous model (2SLS) the model analyzed impact of investment, andinternational trade of Indonesia tourism sector to the national economic growth. Based on the Two StagesLeast Squares method on simultaneous model, the results of the analysis gives some conclusions including: (1)tourism arrivals, tourism expenditure, investment, consumption price index, total consumption, governmentspending, export and import tourism affected the national tourism demand, (2) Current investment andinvestment on previous year, total consumption on previous year, and travel warning have positive impact tonational tourism supply, (3) GDP was the most influenced variable beside Indonesia tourism price andneighbor countries’ tourism price as competitors of Indonesia tourism. Finally, the simulations showed thefiscal and monetary policy impact to the national economic tourismsector.